Implementing of science literacy guidelines for primary school teacher students - Ima Wahyu Putri Utami; Arinta Rezty Wijayaningputri; Nor Hazlina Fazlyn (Research and Development in Education (RaDEn), 2024)
Science literacy is an individual's ability to understand, use, and communicate concepts and critical-thinking in a scientific context. Primary school teacher students plays an important role in shaping strong understanding and effective on science literacy skills among elementary school students. This research employs a qualitative descriptive approach. It utilizes both qualitative and quantitative data. The study focuses on the process of data collection and supporting elements of the research obyek. Data collection techniques in this research include in-depth interviews, observation, and document analysis. The results of this study are a description of the implementation of the implementation of science literacy guidelines that have been effective in helping students understand the material, especially the solar system. The science literacy guide has undergone several revisions and has subsequently made it to the ISBN submission stage. In addition, learning objectives have also been maximally achieved with various activities during the implementation of science literacy books. It can be seen from the results of student work on the students’ worsheet, each group has answered the questions correctly. In addition, the posters that have been made show that the posters are appropriate according to the material that has been studied related to the solar system. While the essays have also been in accordance with the reading material. The implementation of science literacy guidelines can assist the students in acquiring their knowledge, skills, and strategies needes to effectively teach science in elementary schools.